PENGARUH MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS 2 SEKOLAH DASAR - Maherindah Aprilia Mangunsong; Agustina Tyas Asri Hardini (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Elementary school students’ reading comprehension skills remain relatively low. Students are generally able to read texts but experience difficulties in understanding the content, drawing conclusions, and answering implicit questions. This condition indicates the need for the implementation of a learning model that can enhance students’ engagement in comprehending reading texts. The Cooperative Integrated Reading and Composition (CIRC) learning model was selected as an alternative to address this problem. This study aimed to determine the effect of implementing the CIRC learning model on the reading comprehension skills of second-grade elementary school students. This research employed a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The sample consisted of 52 second-grade students at SD Negeri Salatiga 02, selected using purposive sampling. Data were collected through observation and essay tests, then analyzed using normality tests, homogeneity tests, Independent Samples t-Test, and N-Gain Score with the assistance of IBM SPSS Statistics 31. The results showed that the experimental class achieved an average posttest score of 83.58, which was higher than the control class score of 78.85. The Independent Samples t-Test resulted in a significance value of 0.011 < 0.05, indicating that the CIRC model had a significant effect on students’ reading comprehension skills. The N-Gain Score analysis showed that the experimental class was categorized as moderately effective, while the control class was categorized as less effective. The implementation of the CIRC model improved students’ ability to comprehend reading texts through reading activities, discussions, and group collaboration. Therefore, the CIRC model can be used as an alternative approach in Indonesian language learning to improve elementary school students’ reading comprehension skills. ABSTRAK Kemampuan membaca pemahaman siswa sekolah dasar masih tergolong rendah. Siswa umumnya mampu membaca teks, tetapi mengalami kesulitan memahami isi bacaan, menarik kesimpulan, serta menjawab pertanyaan tersirat. Kondisi tersebut menunjukkan perlunya penerapan model pembelajaran yang mampu meningkatkan keterlibatan siswa dalam memahami teks bacaan. Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) dipilih sebagai alternatif untuk mengatasi permasalahan tersebut. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan Model Pembelajaran CIRC terhadap kemampuan membaca pemahaman siswa kelas 2 sekolah dasar. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis quasi eksperimen dan desain Nonequivalent Control Group Design. Sampel penelitian berjumlah 52 siswa kelas 2 SD Negeri Salatiga 02 yang dipilih menggunakan purposive sampling. Data dikumpulkan melalui observasi dan tes uraian, kemudian dianalisis menggunakan uji normalitas, homogenitas, Independent Samples t-Test, dan N-Gain Score berbantuan IBM SPSS Statistics 31. Hasil penelitian menunjukkan bahwa rata-rata posttest kelas eksperimen mencapai 83,58, lebih tinggi dibandingkan kelas kontrol sebesar 78,85. Uji Independent Samples t-Test menghasilkan nilai signifikansi 0,011 < 0,05, sehingga terdapat pengaruh signifikan model CIRC terhadap kemampuan membaca pemahaman siswa. Analisis N-Gain Score menunjukkan kelas eksperimen berada pada kategori cukup efektif, sedangkan kelas kontrol kurang efektif. Penerapan model CIRC mampu meningkatkan kemampuan memahami isi bacaan melalui kegiatan membaca, berdiskusi, dan bekerja sama dalam kelompok. Dengan demikian, model CIRC dapat dijadikan alternatif pembelajaran Bahasa Indonesia untuk meningkatkan kemampuan membaca pemahaman siswa sekolah dasar.